New drugs and the growth of health expenditure: evidence from diabetic patients in Taiwan - Liu, Ya-Ming; Hsieh, Chee-Ruey (Health economics, 2012)
SUMMARY This paper contributes to the growing body of literature that debates whether the adoption of pharmaceutical innovation increases the overall expenditure on health care. By examining data obtained from Taiwan and focusing on diabetic patients, we use a new class of drugs, namely, thiazolidinediones, as an example to investigate the effect on health expenditure of prescribing new drugs to patients by focusing on the impact of treatment substitution and treatment expansion. Overall, our results indicate that the introduction of new drugs mainly impacts the outpatient drug expenditure and does not give rise to any offsetting effect on other outpatient and inpatient health expenditures. This suggests that the adoption of pharmaceutical innovation in treating diabetic patients is expenditure‐increasing. In addition, we find evidence that the treatment substitution channel has a more significant impact on the level of health expenditure than the treatment expansion channel. An important policy implication for our finding is that the justification for increasing health expenditure on the treatment of diabetes is not conditional upon a lowering in the demand for other types of health‐care services. By contrast, it is conditional upon the increased health benefits per se. Copyright © 2011 John Wiley & Sons, Ltd.